CONTINUITY OF CARE WITH A RUPTURE OF THE PERINEUM OF THE SECOND DEGREE IN MRS. F AT THE FRISKA NOVITA PRIMARY CLINIC, MEDAN DISTRICT LABUHAN DELI SERDANG REGENCY YEAR 2025 - Baptisin Hia; Rosmani Sinaga; Amelia Fitri; Clara Deltis; Klarisati; Rosmawar; Daniel Permandan Sitompul (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Perineal rupture is a prevalent obstetric complication, affecting nearly half of global births according to WHO and UNICEF data. It poses significant risks for postpartum hemorrhage and infection, contributing to maternal morbidity rates in Indonesia. Proper management of perineal wounds is crucial to prevent long-term disability and ensure maternal safety.Objective: This study aims to provide and evaluate comprehensive midwifery care for a postpartum patient experiencing a second-degree perineal rupture, utilizing the Continuity of Care (CoC) model and Varney’s seven-step management method.Methods: A descriptive qualitative case study was conducted at Pratama Friska Novita Clinic, Medan, from October 2024 to February 2025. The subject was Mrs. F, a 30-year-old primipara (G1P0A0). Data were collected via observation, physical examination, and interviews. The study followed the patient longitudinally from the third trimester of pregnancy through labor and the puerperium (postpartum period). Results: Mrs. F experienced a second-degree perineal rupture attributed to straining prior to complete cervical dilation during labor. Management involved immediate suturing followed by comprehensive postpartum care. Interventions focused on infection prevention through perineal hygiene education, pain management, and nutritional counseling emphasizing high protein and fiber intake to support tissue repair. The evaluation indicated that the wound healed effectively within the standard 6–7 day timeframe without signs of infection, and the mother reported reduced pain and improved comfort.Conclusion: Comprehensive midwifery care proved effective in managing second-degree perineal ruptures. The study found no discrepancy between theoretical standards and the clinical management provided. It is concluded that proper education on pushing techniques during labor and meticulous postpartum wound care are critical for optimal recovery.